Parking Behavior: Park 'n' Ride (PnR) to encourage multimodalism in Brisbane. (February 2020) - Kimpton, Anthony; Pojani, Dorina; Sipe, Neil; Corcoran, Jonathan
Abstract: 'Park 'n' Ride' facilities (PnR) initially emerged to accommodate motorists that would otherwise exhaust the local supply of parking around train stations and other rapid high occupancy vehicle nodes but increasing became a planning strategy to provide commuters from auto-dependent suburbs with access to rapid high occupancy vehicle to reduce their environmental impacts and inner-city road and parking capacity requirements. Theoretically, PnR should influence modal choice by making the transfer between car and rapid transit more convenient yet this base assumption rarely matches the empirical reality. Our synthesis of the PnR literature suggests that motorists deciding whether to park-and-ride have considerations beyond minimising their travel duration and expenses, and we develop a new integrative model of PnR, multi-modalism, and modal choice to illustrate how reliability and competing transport planning strategies such as inter-city mobility, transit-oriented development, and active transport interact and inform modal choice. Upon laying these theoretical foundations, we empirically examine the extent to which developing or modifying PnR influences modal choice in our case study context, Brisbane, Australia. Our research findings suggest that it is new rather than modified PnR that influence modal choice and that new park and riders are typically drawn from nearby locations rather than peripheral and therefore auto-dependent areas. This influence is particularly evident in suburbs closer to the inner city, and is problematic given that these are not the intended users of PnR. Our synthesis and examination of multi-modalism and modal choice has important implications for researchers, planners, and policy makers attempting to influence modal choice and improve the efficiency of urban mobility.